2015
DOI: 10.9734/jsrr/2015/12046
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Students’ Satisfaction with Their Clinical Placement

Abstract: Introduction: Exposure to positive clinical learning experience influences the nursing students' knowledge, skills, attitudes, and interest in continuing the nursing profession. It is widely acknowledged that clinical placement evaluations while students are on placement is very useful for better understanding of what constitutes quality clinical education from the students' perspective to provide better educational experiences. Aim: The aim of the study was to assess the nursing students' satisfaction with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 41 publications
3
11
0
Order By: Relevance
“…This study explored the experiences of baccalaureate student nurses regarding intra-semester clinical practicum. The findings showed that students perceived intra-semester clinical practicum as beneficial since it afforded the opportunity to translate theory into practice concurrently as previously reported in other studies [ 8 , 10 , 22 ]. For instance, in Saudi Arabia, about 75.6% ( n = 205) of nursing students were satisfied with their clinical practicum [ 10 ].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This study explored the experiences of baccalaureate student nurses regarding intra-semester clinical practicum. The findings showed that students perceived intra-semester clinical practicum as beneficial since it afforded the opportunity to translate theory into practice concurrently as previously reported in other studies [ 8 , 10 , 22 ]. For instance, in Saudi Arabia, about 75.6% ( n = 205) of nursing students were satisfied with their clinical practicum [ 10 ].…”
Section: Discussionsupporting
confidence: 80%
“…The findings showed that students perceived intra-semester clinical practicum as beneficial since it afforded the opportunity to translate theory into practice concurrently as previously reported in other studies [ 8 , 10 , 22 ]. For instance, in Saudi Arabia, about 75.6% ( n = 205) of nursing students were satisfied with their clinical practicum [ 10 ]. The similarities may have resulted from the fact that student nurses recognised nursing as both an art and science and therefore understood the importance of the practical component.…”
Section: Discussionsupporting
confidence: 80%
“…Therefore, [27] Less than half of the nursing students had lower academic self-efficacy; however, this frustrating result was expected as the students affiliated to technical nursing institute were deprived from students' services and activities rendered to other students affiliated to all faculties of the university. Participants of this study were suffering from many problems such as failure to allocate a separate building for them and the current location lacks the existence of essential educational constituents (skills labs, computer labs, language labs, and halls to change clothes and places to eat and enough toilets to accommodate the number of students… etc).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the students' clinical perspective on quality of clinical education contributes to the knowledge for the development of better educational experiences. In addition [26], and [27] highlighted the importance of assessing the clinical learning experiences while students are on placement.…”
Section: Introductionmentioning
confidence: 99%
“…Vice versa Abou elfettoh and Al Mumtin, (2015 ) (15) mentioned that students were dissatisfied with evaluation process from the clinical instructors. This could be attributed to using different stratifies in clinical training in the present study ranked in order of use to; demonstration, simulation, role play, and case study.…”
Section: Discussionmentioning
confidence: 99%